Usaha Peningkatan Kualitas Pelayanan dengan Pendekatan Fuzzy Theory dan Metode Service Quality pada PT. Gadino Sejahtera Abadi Karawang - Sutrisno Sutrisno; Agustian Suseno; Jauhari Arifin (Peneliti.net, 2022)
PT. Gadino Sejahtera Abadi is a type of PLN partner service company because it provides services in the field of electricity administration and connectivity. In addition, it has carried out several activities of the company in an effort to satisfy consumers. This activity is expected to provide efficient results. The purpose of this study is to find out the influence of the quality of customer satisfaction services either together or in part. The type of research used in this study is descriptive research that uses quantitative approaches. The analytical techniques used are descriptive analysis techniques and use multiple regressions. While the sample technique used is a non-probability sample that uses a total sample of 59 people. Based on the results of this study that the quality of service (X) consisting of reliability, certainty, reality, empathy and responsiveness, has a significant influence on customer satisfaction. Some test results show that only variable assurance has some effect on customer satisfaction with a significant number of variables